Экспертно-моделирующая компьютерная система экспресс-энергоаудита электрических сетей облэнерго - Дерзский, В. Г.; Скиба, В. Ф. (НТУ "ХПИ", 2014)
Предлагается инструментарий (методика, алгоритм, программные средства) экспресс-энергоаудита электрических сетей обленерго.

The paper presents instruments (technique, algorithm, software) for express energy audit of electric networks of regional power distribution companies.
Expert computer simulation system for express energy audit of electric networks of regional power distribution companies
Keywords: компьютерная программа; многоцелевая оптимизация; Мировое Энергетическое Агенство; expert; energy audit; computer program; multipurpose optimization